Diagnostic And Treatment Tactics in Gastroesophageal Reflux Disease - Gulamov Olimjon Mirzakhitovich; Ahmedov Gayrat Keldibaevich; Khudaynazarov Utkir Rabbimovich; Saydullayev Zayniddin Yakhshiboyevich (Zien Journals, 2022)
This article analyzes the diagnostic and therapeutic tactics of treating 234 patients with gastroesophageal reflux disease and complicated with various erosive pathologies of the esophageal mucosa, which were investigated in the diagnostic departments of the Samarkand City Medical Association and the State Institution “Republican Specialized Center of Surgery named after academician V. Vakhidov" in the period 2019-2020. Patients, according to indications, were examined in different modes of endoscopic examination (in the usual and in the narrow-spectrum mode (NBI mode).
Keywords: gastroesophageal reflux disease; reflux esophagitis; NBI mode; Barrett's esophagus